2020
DOI: 10.1177/2049936120920177
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral adherence for adolescents growing up with HIV: understanding real life, drug delivery and forgiveness

Abstract: Poorer adherence to medication is normal in adolescence and is one of a range of risk-taking behaviours common during a developmental stage that encompasses enormous cognitive, physical, sexual, social and emotional change. For adolescents living with human immunodeficiency virus (HIV) infection, poor adherence to antiretroviral therapy (ART) confers two significant challenges: poor health, but also the specific additional burden of onward transmission to partners. Late adolescence (15–19 years) is the only ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 75 publications
0
24
0
Order By: Relevance
“…In addition, they tend to solve problems associated with missed doses. In recent years, systems with the capacity to sustain drug release up to years have emerged as ultra-long-acting systems [ 80 , 85 , 121 , 122 , 123 , 124 , 125 ].…”
Section: Nanotechnology Approaches For Hiv/aids Treatmentmentioning
confidence: 99%
“…In addition, they tend to solve problems associated with missed doses. In recent years, systems with the capacity to sustain drug release up to years have emerged as ultra-long-acting systems [ 80 , 85 , 121 , 122 , 123 , 124 , 125 ].…”
Section: Nanotechnology Approaches For Hiv/aids Treatmentmentioning
confidence: 99%
“…In Malawi, a study of depression in ALHIV revealed a prevalence rate of 18.9% [ 1 , 2 , 4 ]. Depression is significantly linked to non-adherence to medication, making its diagnosis and treatment vital in the long-term survival of ALHIV [ 6 , 8 , 10 ]. Despite the high burden of depression and the availability of effective treatments, approximately 60% to 80% of affected adolescents do not receive appropriate care [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Child and adolescent primary care clinics are an important site for the identification of depression in adolescents, the critical first step in connecting youth to treatment [ 3 , 8 , 10 , 11 ]. However, depression remains poorly identified in such settings [ 9 , 10 ]. Research supports the screening of adolescents for depression in primary care [ 7 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations